Interaction between Macrophages and Human Mesenchymal Stromal Cells Derived from Bone Marrow and Wharton's Jelly-A Comparative Study - Marta Dymowska; Aleksandra Aksamit; Katarzyna Zielniok; Monika Kniotek; Beata Kaleta; Aleksander Roszczyk; Michal Zych; Filip Dabrowski; Leszek Paczek; Anna Burdzinska (MDPI AG, 2021)
Despite intensive clinical research on the use of mesenchymal stromal cells (MSCs), further basic research in this field is still required. Herein, we compared human bone marrow MSCs (BM-MSCs, n = 6) and Wharton's jelly MSCs (WJ-MSCs, n = 6) in their ability to interact with human primary macrophages. Evaluation of secretory potential revealed that under pro-inflammatory stimulation, WJ-MSCs secreted significantly more IL-6 than BM-MSCs (2-fold). This difference did not translate into the effect of MSCs on macrophages: both types of MSCs significantly directed M1-like macrophages toward the M2 phenotype (based on CD206 expression) to a similar extent. This observation was consistent both in flow cytometry analysis and immunocytochemical assessment. The effect of MSCs on macrophages was sustained when IL-6 signaling was blocked with Tocilizumab. Macrophages, regardless of polarization status, enhanced chemotaxis of both BM-MSCs and WJ-MSCs (p < 0.01; trans-well assay), with WJ-MSCs being significantly more responsive to M1-derived chemotactic signals than BM-MSCs. Furthermore, WJ-MSCs increased their motility (scratch assay) when exposed to macrophage-conditioned medium while BM-MSCs did not. These results indicate that although both BM-MSCs and WJ-MSCs have the ability to reciprocally interact with macrophages, the source of MSCs could slightly but significantly modify the response under clinical settings.